Effect of anodizing conditions on the cell morphology of anodic films on AA2024‐T3 alloy. (14th September 2018) - Torrescano‐Alvarez, Jeanette M.; Curioni, Michele; Zhou, Xiaorong; Skeldon, Peter
Abstract : The effects of applied current density, anodizing time, and electrolyte temperature on the cell and pore morphology of anodic films and the voltage‐time response obtained during galvanostatic anodizing of AA2024‐T3 alloy in sulphuric acid electrolytes have been studied. Scanning electron microscopy was employed to observe the film morphology. Sponge‐like porous structure was promoted by anodizing at relatively low current density and high electrolyte temperature. In contrast, linear porous structure was favoured under the converse conditions. Intermediate conditions resulted in films containing either sequential layers of the 2 morphologies or a morphology incorporating features of the 2 types; such conditions were associated with anodizing voltages in the range 25 to 35 V. The reasons for the morphological differences are proposed to be due to interactions between film growth stresses and stresses arising from oxygen evolution on the development of the alumina cells.